Physical Abuse Victimization and Violence in the Transition to Adulthood: The Mediating Role of Alcohol and Drug Use. Issue 9 (21st October 2018) - Savage, Joanne; Crowley, Megan Z.
ABSTRACT: In the present paper we examine the association between physical abuse victimization in childhood and violent criminal behavior in the transition from adolescence to adulthood (TAA). Of central interest is whether that association is indirect, through the impact of abuse victimization on alcohol and drug use. We employ a statistical test for indirect effects, using a design that also applies Savage and Wozniak's (2016) "differential etiology of violence" standard. The data suggest that the effect of physical abuse on violence in the TAA is partially indirect, mediated by alcohol and drug use. A control for nonviolent offending is applied to build confidence that the dynamic between abuse victimization and substance use is a differential predictor of violence.